Meta-Analisis Implementasi Landasan Ilmu Pendidikan Dalam Pengembangan E-Modul Fisika Berbasis Pendekatan Sets (Science Environments Technology Society ) Pada Pembelajaran Fisika - Putri, Sri Ramadela; Festiyed, Festiyed (Universitas Negeri Padang, 2019)
This study aims to analyze the implementation of educational science foundation in the development of modules / e-modules based on the SETS (science Environment Technology Society) approach to physics learning. This research method is a meta-analysis with a sample of 20 articles in national and international journals. The results of this meta-analysis are research on the development of modules. SETS-based modules have been widely used. The Developments that have a foundation in sociology and science and technology have been found in many articles while the cultural background is still rarely used than the philosophical and psychological ground